Stedelijk Van Abbemuseum Eindhoven : Beeldende kunst uit de twintigste eeuw. - Leering, Jean; Leering-Van Moorsel, Wies (München, Ahrbeck (Hannover) : Knorr & Hirth Verlag München, Ahrbeck (Hannover), 1969)
Appel, Karel ; Bacon, Francis ; Bazaine, Jean ; Bissière, Roger ; Braque, Georges ; Chagall, Marc ; Corneille ; Delaunay, Robert ; van Doesburg, Theo ; Dubuffet, Jean ; Ernst, Max ; Fontana, Lucio ; Francis, Sam ; Gris, Juan ; Indiana, Robert ; Jorn, Asger ; Kandinsky, Wassily ; Klein, Yves ; Kokoschka, Oskar ; Kruyder, Herman ; Leger, Fernand ; Louis, Morris ; Mack, Heinz ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Ouborg, Pieter ; Permeke, Constant ; Picasso, Pablo ; Poliakoff, Serge ; Stella, Frank ; Tàpies, Antoni ; Zero
Nederlands
boek